2014
DOI: 10.1177/0002716214547476
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Intergenerational Mobility

Abstract: This article reviews the sociological and economic literature on intergenerational mobility. Findings on social class, occupational status, earnings, and income mobility are discussed and discrepancies among them are evaluated. The review also examines nonlinearities in the intergenerational association, variation in mobility across advanced industrial countries, and recent mobility trends in the United States. The literature suggests an association between inequality and economic mobility at the country level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
180
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(189 citation statements)
references
References 120 publications
3
180
1
5
Order By: Relevance
“…In particular, Chetty et al, [2] and Hilger [3] use two different measures of social mobility and both find no trend in US intergenerational mobility from 1980 to 2010 despite a sharp increase in inequality. As Torche [4] argues in her recent comprehensive survey of social mobility in Latin America, these findings create a "conundrum and a challenge" for the Gatsby Curve hypothesis. Even before Harvard's Equality of Opportunity Project findings, Jantti and Jenkins [5] questioned the cross country evidence for the GGC as well.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Chetty et al, [2] and Hilger [3] use two different measures of social mobility and both find no trend in US intergenerational mobility from 1980 to 2010 despite a sharp increase in inequality. As Torche [4] argues in her recent comprehensive survey of social mobility in Latin America, these findings create a "conundrum and a challenge" for the Gatsby Curve hypothesis. Even before Harvard's Equality of Opportunity Project findings, Jantti and Jenkins [5] questioned the cross country evidence for the GGC as well.…”
Section: Introductionmentioning
confidence: 99%
“…Divergences in the patterns and trends of occupational and income mobilities are not particular to Brazil: studies in various other countries also point to this kind of inconsistency (Torche, 2015). For some time scholars of social mobility have been suggesting that these kinds of divergence should be resolved through the use of models and analyses combining occupational and income mobility (Morgan, Grusky & Fields, 2006) and indeed studies are now being developed along these lines (Breen, Mood & Jonsson, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this article I employ this approach to study income mobility. It is important to remember that most studies analyze mobility in terms of wage earnings, but there are also important studies that use family income or income from all sources (Torche, 2015), which would be a more complete measure since it takes into account other incomes coming, for example, from spouses and mothers.…”
Section: Social Mobility: Income Occupation and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the debate about intergenerational mobility and inequality, in the media as well as in the scientific literature (Torche, 2015), authors commonly refer to observed correlations between schooling outcomes and parental characteristics to support their claims or theories. With only one outcome measure at hand this is often the best that can be done.…”
Section: The Raw Correlation Between Parental Education and Achievemementioning
confidence: 99%